STUDI FENOMENOLOGI: MITIGASI BENCANA BERBASIS KEARIFAN LOKAL DESA COLO - Mohammad Khasan; Mochamad Widjanarko; Dian Wismar’ein; Eko Budi Prastyo (Program Studi S1 Psikologi, 2023)
Colo Village is the northernmost village in Kudus Regency, which is geographically located on the slopes of the Muria Mountains and is directly adjacent to the Muria forest with an up and down land contour. Colo Village is included in a disaster village with a history of major disasters such as landslides at several points in 1952 and 2022, as well as forest fires that occurred in 2000. The purpose of this study was to identify disaster mitigation behavior in the community in Colo Village based on local wisdom. The research methodology uses qualitative phenomenology with five informants born and living in Colo Village. This research instrument uses interviews and observations with data analysis coding and triangulation. Based on the results of the study, it shows that disaster mitigation behavior in the form of local wisdom of the Colo Village community is alms earth, barikan, and coffee wiwit. The behavior of disaster mitigation comes from ancestors and is still preserved until now.